2019
DOI: 10.3233/jad-180321
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aβ42 as a Biomarker of Prodromal Alzheimer’s Disease Progression in Patients with Amnestic Mild Cognitive Impairment: Evidence from the PharmaCog/E-ADNI Study

Abstract: It is an open issue whether blood biomarkers serve to diagnose Alzheimer's disease (AD) or monitor its progression over time from prodromal stages. Here, we addressed this question starting from data of the European FP7 IMI-PharmaCog/E-ADNI longitudinal study in amnesic mild cognitive impairment (aMCI) patients including biological, clinical, neuropsychological (e.g., ADAS-Cog13), neuroimaging, and electroencephalographic measures. PharmaCog/E-ADNI patients were classified as "positive" (i.e., "prodromal AD" n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…A lack of correlation between peripheral and central Aβ clearance agrees with observations that reducing peripheral Aβ does not affect brain Aβ levels, or with the absence of correlation between central and peripheral Aβ levels in AD patients (36)(37)(38)(39). However, increased peripheral Aβ levels after anti-Aβ treatment was reported to parallel a decrease of brain Aβ; reducing peripheral Aβ was sufficient to reduced brain Aβ, and recent studies favor a diagnostic utility of the relationship between plasma and CSF Aβ 1-42 (27,40,41). Thus, the relationship between peripheral and central Aβ is still under debate (42); indeed, a substantial part of brain Aβ clearance in humans takes place in the periphery (43).…”
Section: Discussionsupporting
confidence: 72%
“…A lack of correlation between peripheral and central Aβ clearance agrees with observations that reducing peripheral Aβ does not affect brain Aβ levels, or with the absence of correlation between central and peripheral Aβ levels in AD patients (36)(37)(38)(39). However, increased peripheral Aβ levels after anti-Aβ treatment was reported to parallel a decrease of brain Aβ; reducing peripheral Aβ was sufficient to reduced brain Aβ, and recent studies favor a diagnostic utility of the relationship between plasma and CSF Aβ 1-42 (27,40,41). Thus, the relationship between peripheral and central Aβ is still under debate (42); indeed, a substantial part of brain Aβ clearance in humans takes place in the periphery (43).…”
Section: Discussionsupporting
confidence: 72%
“…Studies exploring cognitive associations with longitudinal cohorts of older adults by using highly reliable techniques are still scarce and present multiple methodological differences that prevented reaching a consensus. [17][18][19][20] Further studies are needed to confirm the use of high-accuracy plasma Aβ in associating Aβ levels with cognitive decline to determine the usefulness of this marker in clinical care and research.…”
Section: Introductionmentioning
confidence: 99%
“…Still, others have found no significant relationship [25,26]. Reduced plasma Ab has also been linked to poorer cognition [6,7,19,21,[27][28][29][30]. In addition, some studies have suggested that plasma levels of Ab42 and Ab40 are associated with the levels of cerebral Ab on positron emission tomography (PET), cerebrospinal fluid levels of Ab and tau, and AD-like brain atrophy [4,7,8,11,16,17,24,[31][32][33][34][35][36][37][38], while others have not seen such an association [25,39,40].…”
Section: Introductionmentioning
confidence: 99%